Peningkatan Hasil Belajar Siswa pada Materi Teks Berita Melalui Model Pembelajaran Silent Game - Mutaslimah, Anah (MAN 4 Kota Pekanbaru, 2022)
The completeness of students' cognitive learning outcomes on news text material, especially in linguistic sub-rules, is very low because the learning model is not yet precise. This article aims to improve students' cognitive learning outcomes on news text material in the linguistic rules sub-material with the silent game learning model. The method used is Classroom Action Research with two cycles. Each cycle is carried out in one meeting. The results showed a significant increase in cognitive learning outcomes. Furthermore, there was an increase in the absorption of students from cycle I to cycle II of 18.66. Meanwhile, learning completeness increased by 75% and completeness of objectives and material subjects by 100%. It concludes that the silent game learning model can improve the students' cognitive learning outcomes.